Effects of an environmentally relevant concentration of diuron on oyster genitors during gametogenesis: responses of early molecular and cellular markers and physiological impacts - Akcha, F.; Barranger, A.; Bachère, Evelyne; Heude Berthelin, C.; Piquemal, D.; Alonso, P.; Rondon Sallan, R.; Dimastrogiovanni, G.; Porte, C.; Menard, D.; Szczybelski, A.; Benabdelmouna, A; et al. (Environmental Science and Pollution Research, 2016)
International audience Genitors of the Pacific oyster Crassostrea gigas were submitted during gametogenesis to a short pulse exposure to the herbicide diuron at a realistic environmental concentration. Histological analysis showed no effect of diuron on gametogenesis course, sex ratio and reproductive effort. A non-significant increase in testosterone and progesterone levels was observed in genitors exposed to the herbicide. At cell level, diuron exposure was shown to modulate the phagocytic activity of circulating hemocytes. The results of a transcriptional analysis showed that diuron affected the expression of genes belonging to functions known to play a major role during oyster gametogenesis such as gene transcription regulation, DNA replication and repair, DNA methylation and cytokinesis. Taking into account the results we previously obtained on the same genitors, this study showed a negative effect of diuron on oyster reproduction by inducing both structural and functional modifications of the DNA